Extending knowledge of the clinical picture of Balkan adder (Vipera berus bosniensis) envenoming: The first photographically-documented neurotoxic case from South-Western Hungary. (1st March 2018) - Varga, Csaba; Malina, Tamás; Alföldi, Viktória; Bilics, Gergely; Nagy, Ferenc; Oláh, Tibor
Abstract: We report a severe envenoming associated with minimal local symptoms following a Balkan adder ( Vipera berus bosniensis ) bite in South-Western Hungary. A 63-year-old male with a history of hypertension and sinus bradycardia (45/min) was bitten by a sub-adult specimen of V. b. bosniensis in Somogy County on 04 May 2017. The patient was transported to and treated at the Emergency Department of "Moritz Kaposi" General Hospital, Kaposvár. Locally only pain and minimal swelling with a small haematoma developed on the bitten finger. The abdominal muscles were very tender and guarding was detected upon palpation on the way to hospital. The patient, who had taken his telmisartan (80 mg) tablet in that morning, complained of nausea and dizziness during the first medical examination. The systemic signs included fluctuations in blood pressure (115/85–165/105 mmHg), ECG changes (transient horizontal ST depression in V5-6, and sinus tachycardia (90/min)), severe diarrhoea and vomiting (in 7 episodes). Descending neuromuscular paralysis appeared in the next morning, including complete bilateral ptosis with external ophthalmoplegia, and binocular diplopia. Single-fiber electromyography confirmed the neuromuscular block in the frontalis muscle innervated by the facial nerve. Intense dizziness with uncoordinated movement emerged on the 3rd day. The laboratory findings were mild, including anaemia, hypokalaemia, elevated glutamic-pyruvic transaminase and C-reactive protein levels. The absolute neutrophil count remained almost completely normal. Supportive care and monovalent antivenom (Viper Venom Antitoxin ®, Biomed, Warsaw) were applied. The patient was discharged from hospital on the 4th day, although recovery was not complete until 9 days after the bite. This is the first photographically-documented case of neurotoxic envenoming from the South-Western Hungarian distribution range of V. b. bosniensis . Highlights: We report a severe envenoming with minimal local symptoms following a Balkan adder ( Vipera berus bosniensis ) bite. Gastrointestinal symptoms, dizziness, ECG changes, and fluctuated blood pressure developed with mild laboratory findings. Descending neuromuscular paralysis involved complete bilateral ptosis, ophthalmoplegia and binocular diplopia. SfEMG was performed on the patient, and confirmed the neuromuscular block in the facial nerve innervated frontalis muscle. It is the first photographically-documented neurotoxic bite from the northernmost distribution range of V. b. bosniensis.